PERSEPSI PETANI TEBU TERHADAP PENERAPAN SISTEM PEMBELIAN TEBU (SPT): STUDI KASUS DI KABUPATEN SITUBONDO - Annur Galih Yusvianto; Ebban Bagus Kuntadi (JSEP (Journal of Social and Agricultural Economics), 2022)
Sugarcane is one of the leading plantation commodities in Situbondo Regency, especially in the Asembagus District. Generally, sugarcane farmers sell sugar cane to sugar factories using a profit-sharing system (SBH). In 2019, the government implemented a new partnership system for sugar cane farmers and sugar factories, namely the sugar cane purchase system (SPT), which will replace the profit-sharing system (SBH). This study aims to determine the perception of sugarcane farmers on implementing the sugarcane purchasing system (SPT) and the factors influencing the perceptions of sugarcane farmers in the Asembagus District. This research method is descriptive-analytic with measurement tools using a Likert scale and data analysis using multiple linear regression. The results showed 1) The perception of sugarcane farmers towards implementing the sugarcane purchasing system (SPT) was expressed by several indicators that cumulatively had a score of 3.777 out of 7.380, where sugarcane farmers perceived that the implementation of the SPT system, in general, had a positive impact. 2) The factors that influence the perception of sugarcane farmers have met the classical assumption test with the factors that significantly influence the length of farming, farmer education, and job diversification. In contrast, the non-significant factors are farmer age, land area, and land status.